2017
DOI: 10.1111/imb.12322
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of female‐biased odorant binding protein 6 for volatile and nonvolatile host compounds in Adelphocoris lineolatus (Goeze)

Abstract: The polyphagous mirid bug Adelphocoris lineolatus relies heavily on olfactory cues to track suitable host plants. Thus, a better understanding of the molecular basis of its olfactory detection could contribute to the development of effective pest management strategies. In the present study, we report the expression profile of the odorant binding protein gene A. lineolatus odorant binding protein 6 (AlinOBP6). Quantitative real-time PCR experiments suggest that AlinOBP6 is female adult antennae-biased. Cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 70 publications
(108 reference statements)
1
20
0
Order By: Relevance
“…To date, two OBPs in A. lineolatus have been implicated in the perception of bitter substances, such as catechin and quercetin. One is the antennal contact sensilla-expressed AlinOBP6 (Sun et al, 2017b ), and the other is AlinOBP11, which is expressed highly in mouthparts (Sun et al, 2016 ) and the tarsal gustatory sensillum lymph of Sch2 (Figures 5K–N ). These results indicate that mirid bug species, at least for A. lineolatus have evolved a complex gustatory repertoire to perceive important taste substances for host plant-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, two OBPs in A. lineolatus have been implicated in the perception of bitter substances, such as catechin and quercetin. One is the antennal contact sensilla-expressed AlinOBP6 (Sun et al, 2017b ), and the other is AlinOBP11, which is expressed highly in mouthparts (Sun et al, 2016 ) and the tarsal gustatory sensillum lymph of Sch2 (Figures 5K–N ). These results indicate that mirid bug species, at least for A. lineolatus have evolved a complex gustatory repertoire to perceive important taste substances for host plant-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms of A. lineolatus olfaction, in particular OBP identification and their binding repertoires to plant volatiles have been extensively studied (Gu et al, 2011b ; Sun L. et al, 2013 ; Sun et al, 2014b ). Interestingly, we found that antennae-enriched or mouthpart-biased OBPs potentially bind to non-volatile plant secondary metabolites (Sun et al, 2016 , 2017b ). Mirid species reportedly contact the host plant surface via foreleg tarsi, and therefore, it is reasonable to hypothesize that OBPs expressed on tarsi help mirid bugs to respond to contact substances on host plant surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 12 of 14 OBPs in A. lineolatus (Gu et al, 2011), 21 of 33 OBPs in L. lineolaris (Hull et al, 2014), five of nine OBPs in A. gossypii (Gu, Wu, et al, 2013), seven of 13 OBPs in S. avenae (Xue et al, 2016) and at least six of 10 OBPs in N. lugens (Zhou et al, 2014) were highly expressed in the antennae of insects. In the present study, 24 of 33 EonuOBPs were primarily or uniquely expressed in the antennae of E. onukii than that in the body (Figure 4) (Sun, Wang, Yang, et al, 2017). Moreover, one subclass of OBP families named pheromone binding proteins (PBPs) was highly abundant in antenna and showed high binding affinity to insect sex pheromones (Gu, Zhou, Wang, Zhang, & Guo, 2013).…”
Section: Discussionmentioning
confidence: 57%
“…So far, various investigations suggested that antenna‐enriched OBPs played crucial roles in the olfactory perception process. For instance, an antenna‐enriched OBP (AlinOBP6) can bound tightly to host plant volatile and non‐volatile compounds (host secondary metabolites), implying AlinOBP6 related to host plant detection and location (Sun, Wang, Yang, et al., ). Moreover, one subclass of OBP families named pheromone binding proteins (PBPs) was highly abundant in antenna and showed high binding affinity to insect sex pheromones (Gu, Zhou, Wang, Zhang, & Guo, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving OBP identification (Li L. et al, 2017;Zhao et al, 2018), protein structural analysis (Northey et al, 2016;Falchetto et al, 2019), immunocytochemistry in specific olfactory sensilla Zhang et al, 2018), ligand binding properties (Sun et al, 2017(Sun et al, , 2018, and in vivo RNA interference (Yin et al, 2018;He et al, 2019) have demonstrated that insect OBPs play crucial roles in odorant discrimination, binding, and transportation. These proteins carry lipophilic odorants to the olfactory receptor cells in the sensillar lymph surrounding the sensory dendrite (Pelosi et al, 2014(Pelosi et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%